2008
DOI: 10.1007/s11273-008-9107-5
|View full text |Cite
|
Sign up to set email alerts
|

Sawgrass (Cladium jamaicense) responses as early indicators of low-level phosphorus enrichment in the Florida Everglades

Abstract: Anthropogenic phosphorus (P) inputs to the Florida Everglades have produced dramatic changes in the wetland vegetation of this otherwise oligotrophic system. While the proliferation of undesirable plant species in response to enrichment has been well documented, nutrient-related changes in the physiological and morphological attributes of existing vegetation, prior to any shifts in species composition or changes in the spatial extent of certain taxa, have yet to be adequately characterized. In this experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This difference in N:P ratios arises also because of differences in species composition, although both hammock types predominantly have Neotropical hardwoods. Other plant communities and species in the Everglades can have ratios higher than that in tree island hammocks, such as approximately 42 for pine rocklands (Saha et al 2009) and 27-84 for sawgrass (Miao and Sklar 1998;Richardson et al 1999;Smith et al 2009) in the northern Everglades, thus supporting the idea of tree islands as localized phosphorus hotspots in the otherwise extremely oligotrophic Everglades landscape.…”
Section: Plant Communities and Foliar Nutrientsmentioning
confidence: 91%
“…This difference in N:P ratios arises also because of differences in species composition, although both hammock types predominantly have Neotropical hardwoods. Other plant communities and species in the Everglades can have ratios higher than that in tree island hammocks, such as approximately 42 for pine rocklands (Saha et al 2009) and 27-84 for sawgrass (Miao and Sklar 1998;Richardson et al 1999;Smith et al 2009) in the northern Everglades, thus supporting the idea of tree islands as localized phosphorus hotspots in the otherwise extremely oligotrophic Everglades landscape.…”
Section: Plant Communities and Foliar Nutrientsmentioning
confidence: 91%
“…Exotics and cattail exhibited still lower agreement accuracies and higher variability than most canopied wetland environments. Tending to occur along canals and levees, such locations in the normally oligotrophic Everglades often exhibit relatively enhanced vegetation growth, higher density and increased cover due to the leaching of nutrients (mainly phosphorus) from the canals [68][69][70][71][72][73][74]. Therefore, this community persists in areas of altered water quality over deeper, dynamically inundated ground.…”
Section: Community Level Differencesmentioning
confidence: 99%
“…In contrast, the high d 15 N at the impacted sites was due to P enrichment which leads to high N demand and low 15 N fractionation. Many studies have demonstrated that P is the limiting nutrient in the Everglades (e.g., Newman et al, 1996Smith et al, 2009. Recent studies using stable isotopes found a positive relationship between TP and d 15 N of periphyton, sawgrass and cattail in WCA-1 and WCA-2A, which was attributed to P-driven plant growth and reduced isotope fractionation (Inglett and Reddy 2006;Chang et al, 2009).…”
Section: Biota D 15 N As An Indicator For Eutrophicationmentioning
confidence: 99%